GC-MS Analysis and Biomedical Therapy of Oil from n-Hexane Fraction of Scutellaria edelbergii Rech. f.: In Vitro, In Vivo, and In Silico Approach - Muddaser Shah; Waheed Murad; Najeeb Ur Rehman; Sidra Mubin; Jamal Nasser Al-Sabahi; Manzoor Ahmad; Muhammad Zahoor; Obaid Ullah; Muhammad Waqas; Saeed Ullah; Zul Kamal; Rafa Almeer; et al. (Molecules, 2021)
The current study aimed to explore the crude oils obtained from the n-hexane fraction of Scutellaria edelbergii and further analyzed, for the first time, for their chemical composition, in vitro antibacterial, antifungal, antioxidant, antidiabetic, and in vivo anti-inflammatory, and analgesic activities. For the phytochemical composition, the oils proceeded to gas chromatography-mass spectrometry (GC-MS) analysis and from the resultant chromatogram, 42 bioactive constituents were identified. Among them, the major components were linoleic acid ethyl ester (19.67%) followed by ethyl oleate (18.45%), linolenic acid methyl ester (11.67%), and palmitic acid ethyl ester (11.01%). Tetrazolium 96-well plate MTT assay and agar-well diffusion methods were used to evaluate the isolated oil for its minimum inhibitory concentrations (MIC), minimum bactericidal concentration (MBC), half-maximal inhibitory concentrations (IC50), and zone of inhibitions that could determine the potential antimicrobial efficacy’s. Substantial antibacterial activities were observed against the clinical isolates comprising of three Gram-negative bacteria, viz., Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa, and one Gram-positive bacterial strain, Enterococcus faecalis. The oils were also effective against Candida albicans and Fusarium oxysporum when evaluated for their antifungal potential. Moreover, significant antioxidant potential with IC50 values of 136.4 and 161.5 µg/mL for extracted oil was evaluated through DPPH (1,1-Diphenyl-2-picryl-hydrazyl) and ABTS assays compared with standard ascorbic acid where the IC50 values were 44.49 and 67.78 µg/mL, respectively, against the tested free radicals. The oils was also potent, inhibiting the α-glucosidase (IC50 5.45 ± 0.42 µg/mL) enzyme compared to the standard. Anti-glucosidase potential was visualized through molecular docking simulations where ten compounds of the oil were found to be the leading inhibitors of the selected enzyme based on interactions, binding energy, and binding affinity. The oil was found to be an effective anti-inflammatory (61%) agent compared with diclofenac sodium (70.92%) via the carrageenan-induced assay. An appreciable (48.28%) analgesic activity in correlation with the standard aspirin was observed through the acetic acid-induced writhing bioassay. The oil from the n-hexane fraction of S. edelbergii contained valuable bioactive constituents that can act as in vitro biological and in vivo pharmacological agents. However, further studies are needed to uncover individual responsible compounds of the observed biological potentials which would be helpful in devising novel drugs.